Wood density of trees in black water floodplains of Rio Jaú National Park, Amazonia, Brazil - PAROLIN,Pia (2000)
The Jaú National Park is the largest protected forested area in the world. The Vitória Amazônica Foundation is working towards understanding its ecosystem, to which this paper contributes. Wood density was analysed in 27 common tree species growing in the blackwater flood-plains of the Rio Jaú, an affluent of the Rio Negro (Amazonia, Brazil). Wood was sampled with an increment borer. Mean wood density of the analysed species ranged from 0.35 to 0.87 g cm-3. The mean of all sampled species was 0.67 g cm-3 (st. dev. 0.13). Lowest density was found for Hevea spruceana with 0.32 g cm-3 and highest for Crudia amazonica with 0.9 g cm-3.